Observation of Coherent Transition Radiation in Super-radiant Regime and its Application for Longitudinal Diagnostics; Young Scientists and Specialists (AYSS-2024) - Kubankin A. S. Aleksandr Sergeevich; Baldin A. A. Anton Aleksandrovich; Klenin A. A. Artemy; Kidanova E. A. Ekaterina Alekseevna; Bushmina E. A. Elizaveta Alekseevna; Kishin I. A. Ivan; Nozdrin M. A. Mikhail; Karataev P. V. Pavel Vladimirovich; Alekseev S. V. Sergei; Stuchebrov S. G. Sergey Gennadevich; Kocharian (Kocharyan) V. R. Vagan Rashidovich; Margaryan V. Vardan; et al. (2024, 2024)
Electromagnetic radiation in millimetre and sub-millimetre wavelength range is a area of intense studies due to its application for longitudinal beam diagnostics and for generation of intense radiation beams. Transition radiation (TR) appearing when a fast charge particle crosses an vacuum-matter interface is one of the mechanism broadly used for this purpose, because its spectral angular distribution has been invested in details during the past few decades. Deep understanding of TR properties enables us to predict its behaviour in a broad range of electron beam parameters including energy from non-relativistic to ultra-relativistic region, beam sizes form sub-micron to hundreds of microns, angular divergence form micro- to miliradians, etc